A alfabetização em Moçambique: desafios da educação para todos - Mário, Mouzinho; Nandja, Débora (UNESCO, 2006)
This paper was commissioned by the Education for All Global Monitoring Report as background information to assist in drafting the 2006 report.
Keywords: Alfabetização; Moçambique